2012
DOI: 10.1371/journal.pone.0035158
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of miR-205 in Endometrial Cancer

Abstract: PurposemicroRNAs have emerged as key regulators of gene expression, and their altered expression has been associated with tumorigenesis and tumor progression. Thus, microRNAs have potential as both cancer biomarkers and/or potential novel therapeutic targets. Although accumulating evidence suggests the role of aberrant microRNA expression in endometrial carcinogenesis, there are still limited data available about the prognostic significance of microRNAs in endometrial cancer. The goal of this study is to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
81
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 48 publications
9
81
0
Order By: Relevance
“…2B). This shows that miR-205 was down-regulated significantly in the KB oral cancer cells as well as in other cancer cells, such as melanoma Xu et al, 2012), bladder cancer , prostate carcinoma (Boll et al, 2012), endometrial cancer (Karaayvaz et al, 2012) and breast cancer (Adachi et al, 2011). These results suggest that over-expressed miR-205 would increase the level of apoptotic cell death in KB cells.…”
Section: Resultsmentioning
confidence: 75%
“…2B). This shows that miR-205 was down-regulated significantly in the KB oral cancer cells as well as in other cancer cells, such as melanoma Xu et al, 2012), bladder cancer , prostate carcinoma (Boll et al, 2012), endometrial cancer (Karaayvaz et al, 2012) and breast cancer (Adachi et al, 2011). These results suggest that over-expressed miR-205 would increase the level of apoptotic cell death in KB cells.…”
Section: Resultsmentioning
confidence: 75%
“…Like this article, other three studies estimated the prognostic value of miRNA 200c expression in tumor tissue (Yu et al, 2010;Marchini et al, 2011;Karaayvaz et al, 2012). Among these studies, two studies reported HR and its 95% CI (Marchini et al, 2011;Toiyama et al, 2013) and the rest ones were processed by Matthew Sydes and Jayne Tierney's method to acquire survival data (Tierney et al, 2007;Marchini et al, 2011;Karaayvaz et al, 2012). HRs (high vs low) were pooled by fixedeffects model ( Figure 2B, …”
Section: Tissue Mirna 200c Expression and Survivalmentioning
confidence: 98%
“…A number of recent studies have investigated the expression profiles of miRNAs in endometrial cancer Cohn et al, 2010;Ratner et al, 2010;Snowdon et al, 2011). Several studies reported elevated expression level of miR-205 in different types of endometrial cancer compared to normal endometrial tissues and plasmas (Boren et al, 2008;Hiroki et al, 2010;Karaayvaz et al, 2012). Its aberrant expression is proved to be associated with advanced stage in endometrial cancer (Chung et al, 2009), and with overall ratio of survival such that patients with higher levels of miR-205 tend to have a worse survival phenotype (Karaayvaz et al, 2012).…”
Section: Mir-205 In Endometrial Cancermentioning
confidence: 99%
“…Several studies reported elevated expression level of miR-205 in different types of endometrial cancer compared to normal endometrial tissues and plasmas (Boren et al, 2008;Hiroki et al, 2010;Karaayvaz et al, 2012). Its aberrant expression is proved to be associated with advanced stage in endometrial cancer (Chung et al, 2009), and with overall ratio of survival such that patients with higher levels of miR-205 tend to have a worse survival phenotype (Karaayvaz et al, 2012). miR-205 is further confirmed to negatively regulate cellular proliferation, migration and invasion properties (Su et al, 2013), with this regard, a number of target mRNAs are investigated to be associated with miR-205 in endometrial cancer.…”
Section: Mir-205 In Endometrial Cancermentioning
confidence: 99%
See 1 more Smart Citation